2015
DOI: 10.1182/blood-2015-07-658823
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HGF/c-MET induces cell cycle arrest, DNA damage, and apoptosis for primary effusion lymphoma

Abstract: Key Points The HGF/c-MET pathway has a complex network to control KSHV+ PEL cell survival. The c-MET inhibitor induces PEL apoptosis and suppresses tumor progression in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…The top 30 up-regulated and down-regulated candidate genes were listed in Table 1 and 2, respectively. Among these candidates, there are several notable features: 1) some nuclear small RNA transcripts such as RN7SK, RNU1G2, RNU1–5, RNU1–3 and RNU1A3 are highly up-regulated, which has also been observed in c-MET inhibitor treated KSHV+ PEL tumor cells in spite of unknown mechanisms or functions (20); 2) multiple Metallothionein genes such as MTE, MT1F/E/G and MT2A are significantly up-regulated, and they have been shown to be increased during oxidative stress (21, 22) to protect the cells against cytotoxicity (23, 24), radiation and DNA damage (25, 26), and be increased in a variety of human tumors (27); 3) some genes have been reported related to tumor cell proliferation, such as PPM1D , silencing of which by RNAi inhibits lung cancer cells proliferation and the tumorigenicity of bladder cancer cells, respectively (28, 29). However, we found that the functional role of most genes listed here remains unclear for KSHV pathogenesis or tumorigenicity, which requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The top 30 up-regulated and down-regulated candidate genes were listed in Table 1 and 2, respectively. Among these candidates, there are several notable features: 1) some nuclear small RNA transcripts such as RN7SK, RNU1G2, RNU1–5, RNU1–3 and RNU1A3 are highly up-regulated, which has also been observed in c-MET inhibitor treated KSHV+ PEL tumor cells in spite of unknown mechanisms or functions (20); 2) multiple Metallothionein genes such as MTE, MT1F/E/G and MT2A are significantly up-regulated, and they have been shown to be increased during oxidative stress (21, 22) to protect the cells against cytotoxicity (23, 24), radiation and DNA damage (25, 26), and be increased in a variety of human tumors (27); 3) some genes have been reported related to tumor cell proliferation, such as PPM1D , silencing of which by RNAi inhibits lung cancer cells proliferation and the tumorigenicity of bladder cancer cells, respectively (28, 29). However, we found that the functional role of most genes listed here remains unclear for KSHV pathogenesis or tumorigenicity, which requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…PEL is a rapidly progressing malignancy with a median survival time of approximately 6 months even under the conventional chemotherapy [36]. Co-expression of HGF and c-MET was found in all KSHV+ PEL cell lines [32, 37]. HGF stimulation of PEL cells rapidly induces c-MET tyrosine phosphorylation [30].…”
Section: The Expression/activation Of Hgf/c-met In Different Types Ofmentioning
confidence: 99%
“…HGF stimulation of PEL cells rapidly induces c-MET tyrosine phosphorylation [30]. Our recent study found that KSHV de novo infection greatly induced HGF production and the phosphorylation of c-MET from primary endothelial cells [37]. In HIV-infected patients, KSHV-positive group had higher plasma HGF concentration than those from the KSHV-negative group [37].…”
Section: The Expression/activation Of Hgf/c-met In Different Types Ofmentioning
confidence: 99%
See 2 more Smart Citations